William Hughes Australia - Bridge, Carl (Haus histories, 2011)
World War I marked the emergence of the Dominions on the world stage as independent nations, none more so than Australia. This book shows the beginnings of its autonomy, from with their national awakening following the country's sacrifice at Gallipoli in 1915 to Versailles and beyond.